The Evaluation of UPro as a New Nutrient on High-Quality Egg Production From the Perspective of Egg Properties, Intestinal Histomorphology, and Oviduct Function of Laying Hens - Chang, Xinyu; Qiu, Kai; Wang, Jing; Zhang, Haijun; You, Shizhou; Mi, Shuichao; Qi, Guanghai; Wu, Shugeng (Frontiers in Nutrition, 2021)
This study was to investigate the effects of UPro as a new nutritive fortifier on high quality eggs production from the perspective of egg properties, intestinal histomorphology and oviduct function of laying hens. The evaluation of UPro Four hundred thirty-two Hy-Line Brown laying hens aged 56 wks were allocated to 4 groups. Layers were given a basal diet or supplemented with different levels of small peptides (0.2%, 0.4%, and 0.8%) to replace soybean meal. After 1-week adaptation period, the feeding trial was conducted for 12 weeks. The results showed that UPro addition significantly decreased (P < 0.05) the hardness, stickiness, and chewiness of albumen of layers on weeks 12. A linear elevation (P < 0.05) in the albumen height, Haugh unit (HU), and crude protein content of albumen of layers were noted on week 12 along with dietary UPro addition increased, the villus height (VH) and villus height-to-crypt depth radio (VCR) of jejunum were also linearly increased (P < 0.05). Besides, there were linear elevations (P < 0.05) in the relative mRNA expression of SEC23 homolog A (SEC23A) and protein-O-mannosyltransferase1 (POMT1) in layers as dietary UPro addition increased. In conclusion, dietary UPro addition could improve intestinal health, increase the absorption of nutrients, and improve egg quality of laying hens. The possible mechanism underlying that UPro improves the quality and processing characteristics of albumen is up-regulating SEC23A and POMT1 expression of magnum. These findings will promote the application of Upro as a new nutritional additive in the production of high quality eggs.